ANALISIS KELAYAKAN BISNIS PADA UMKM KEDAI BABEH DI TINJAU DARI ASPEK PASAR DAN PEMASARAN - Ariyantiningsih, Febri; Darmawan, Muh. Bayu; Rahmadani, Muhammad; Wahyuni, Sri (Fakultas Ekonomi dan Bisnis, 2025)
Micro, small, and medium enterprises (MSMEs) in the culinary sector play a strategic role in driving the regional economy, particularly in creating jobs and meeting the community's consumption needs. One of the main challenges for culinary MSMEs is ensuring their businesses have market feasibility and appropriate marketing strategies to survive and thrive amidst competition. This study aims to analyze the business feasibility of Kedai Babeh MSMEs from a market and marketing perspective. The research method used is descriptive qualitative with a case study approach. Data collection techniques were carried out through in-depth interviews with the owner and customers, direct observation of operational and marketing activities, and documentation. The results show that Kedai Babeh has quite large market potential with the main segmentation being students and workers around the business location. However, the marketing strategy implemented is still conventional and has not been systematically planned. Therefore, strengthening marketing strategies through the use of digital media, product differentiation, and strengthening brand identity is needed to assess the business's viability and sustainability.